Conciliación entre el papel de la mujer como madre y trabajadora, en organizaciones de Educación Superior de la ciudad de Tunja, Boyacá - Fonseca Barrera, Andrea Carolina (Universidad Pedagógica y Tecnológica de Colombia, 2024)
Eng: This research pursue the problem of reconciliation between the productive world and motherhood, based on a documentary review of a descriptive nature, and phenomenological reviw, adopting a biographical - narrative method, which was sought from the action of telling, give voice to the women protagonists of the present investigation. The narrative report that will include the results of the application of a questionnaire and an in-depth interviews, that give an account of the difficulties that women find in the search of the conciliation between their roles as woman in leadership role and as a mothers, the tensions that they generate and the strategies they must develop in order to harmonize both facets. This study inquired about labor policies of labor maternity conciliation in Colombia and internationally, and practices organizations, which can become an obstacle to the full and equitable development of women.